Sulle riscritture intersemiotiche: Beowulf al cinema e a teatro (Altre Modernità, 2012)
Following Even-Zohar’s (1979ff.) theoretical framework, particularly as regards his theory of ‘transfer’ (i.e. a text which was created in a cultural system A is re-created in a cultural system B), this essay analyses some modern cinematic and theatrical adaptations of the Old English epic poem Beowulf. Even-Zohar’s theory of transfer has been seldom used in previous research dealing with intersemiotic translation, some notable exceptions being Cattrysse (1992), Remael (2000), and Weissbrod (2004), (2006). After discussing the peculiarities of the processes of transfer applied to medieval works, the reasons why Beowulf can still nowadays play the role of an imported good and, through its rewrites, is integrated into the home repertoire of a contemporary cultural polysystem will be discussed, along with the consequences generated by this integration. Furthermore, the network of relations between the state of the home system, the nature of the transference activity, and the relations between power and market with respect to the ideological component of the process of tranfer will be taken into consideration. To this end, the notions of ‘capital’ elaborated by Bourdieu (1980), as well as that of ‘norm’ put forth by Toury ([1978] 1995) will be used. The results achieved in this study are in line with the claim that peculiar processes affecting specific form of intersemiotic translation can be detected only within the framework of a general theory of transfer.